(untitled) (Scientific journal of the Fergana State University, 2026)
The article offers an integrative study of the cultural-historical meanings of symbols and signs functioning in the contemporary information space, grounded in a stratified model of cultural semantics (cultural seme — cultural connotation — cultural concept — cultural background) and a differential-integrative approach that combines structural and anthropological perspectives. The practical section analyzes the cultural-historical layers and pragmatic functions of widely used graphic and pictographic signs: the “heart” as a like indicator, the “thumbs up,” the “lock” as an index of security/closedness, the “magnifying glass” as a metaphor of search, the “paperclip” as an attachment sign, the “bell” as a notification, the “cloud” as a metaphor of distributed storage, and the QR code as an industrial pictogram that has migrated into mass communication. It is shown that each of these signs realizes the principle of cultural memory and “explosions” of meanings: historical connotations are re-coded by digital practices, and evaluative valence shifts depending on genre, platform, and the audience’s ideological settings.